(untitled) (The International Journal of Language Studies (ISSN : 3078 - 2244), 2024)
Technology integration is vital in modern education, as it enhances engagement and interaction. This study explores the impact of the flipped classroom model and Kahoot! on improving vocabulary retention for pre-intermediate students in Gold B1 Preliminary Lesson 2 of Unit 1. In the flipped classroom approach, students learn new material independently at home through online resources, freeing classroom time for activities that solidify understanding. Kahoot!, a game-based platform, further enhances this learning environment by fostering student motivation and concentration through interactive quizzes. Combining these methods allows students to work at their own pace and apply vocabulary in a competitive, enjoyable setting. The findings underscore the value of incorporating technology into vocabulary instruction, showcasing its ability to foster efficient and effective learning experiences. The study concludes with recommendations for educators to consider thoughtful integration of technology to improve student engagement and learning outcomes, emphasizing that innovative strategies like these can significantly boost educational quality.